Case report: CAR-T cell therapy-induced cardiac tamponade - Sarfati, Sacha; Norbert, Misa Eugène; Hérault, Antoine; Giry, Marion; Makké, Jade; Grall, Maximilien; Savouré, Arnaud; Camus, Vincent; Alani, Mustafa; Tamion, Fabienne; Latouche, Jean-Baptiste; Girault, Christophe (Frontiers in Cardiovascular Medicine, 2023)
CD19-specific chimeric antigen receptor T (CAR-T) cell therapy has recently been shown to improve the prognosis of refractory diffuse large B-cell lymphoma (DLBCL). However, CAR-T cells may induce numerous adverse events, in particular cytokine release syndrome (CRS) which is frequently associated with cardiovascular manifestations. Among the latter, acute pericardial effusion represents less than 1% of cases and cardiac tamponade has only been reported once. The management and outcome of these severe complications are not well established. We report here, a case of cardiac tamponade associated with CRS in a context of CAR-T cell therapy, which required urgent pericardiocentesis. Case summary A 65-year-old man with refractory DLBCL was treated with CAR-T cell therapy. He had a history of dilated cardiomyopathy with preserved ejection fraction and transient atrial fibrillation. A pericardial localization of the lymphoma was observed on the second relapse. One day after CAR-T cell infusion the patient was diagnosed with grade 1 CRS. Due to hypotension, he was treated with tocilizumab and dexamethasone, and then transferred to intensive care unit (ICU). Echocardiography performed at ICU admission showed acute pericardial effusion with signs of right ventricular heart failure due to cardiac tamponade. It was decided to perform pericardiocentesis despite grade IV thrombocytopenia in a context of aplasia. Analysis of pericardial fluid showed a large number of lymphoma cells and 73% of CAR-T cells amongst lymphocytes, a level that was similar in blood. Hemodynamic status improved after pericardiocentesis, and no recurrence of pericardial effusion was observed. The presence of a high count of activated CAR-T cells in the pericardial fluid as well as the short interval between CAR-T cells injection and the symptoms appear as potential arguments for a direct action of CAR-T cells in the mechanism of this adverse event. The patient was discharged from ICU after two days and initially exhibited a good response to DLBCL treatment. Unfortunately, he died fifty days after starting CAR-T cell therapy due to a new DLBCL relapse. Conclusion Patients with a pericardial localization of DLBCL should be assessed for a risk of cardiac tamponade if receiving CAR-T cell therapy and presenting CRS. In this case, cardiac tamponade seems directly related to CAR-T cell expansion. Pericardiocentesis should be considered as a feasible and effective treatment if the risk of bleeding is well controlled, in association with anti-IL6 and corticosteroids.